1993
DOI: 10.3109/10611869308996084
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of [18F]Fluoroalanine and [18F]Fluorotamoxifen for Imaging Breast Tumors

Abstract: To develop ligands for imaging breast tumors, [18F]fluoro analogue of tamoxifen and [18F]fluoroalanine were radiosynthesized. In vivo biodistribution studies were performed in mammary tumor-bearing rats. In studies on the biodistribution of an [18F]fluoro analogue of tamoxifen, tumor uptake decreased when rats were pretreated with diethylstilbestrol (DES), suggesting that tracer uptake in tumors was receptor-mediated. An estrogen receptor assay indicated that tumors have a receptor density of 7.5 fmol/mg prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…However, few studies compared these radiopharmaceuticals with other diagnostic methods. Those radiolabeled amino acids studied in breast cancer include L-[ 18 F]α-methyltyrosine [96], [ 11 C]methionine [96,97], [ 18 F]fluoroalanine [98] and [ 11 C]tyrosine [99]. During chemotherapy courses, the uptake of [ 11 C]methionine from metastases decreased in cases of stable or responsive disease and increased in cases of progressive disease [97].…”
Section: Radiolabeled Nucleosides and Amino Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies compared these radiopharmaceuticals with other diagnostic methods. Those radiolabeled amino acids studied in breast cancer include L-[ 18 F]α-methyltyrosine [96], [ 11 C]methionine [96,97], [ 18 F]fluoroalanine [98] and [ 11 C]tyrosine [99]. During chemotherapy courses, the uptake of [ 11 C]methionine from metastases decreased in cases of stable or responsive disease and increased in cases of progressive disease [97].…”
Section: Radiolabeled Nucleosides and Amino Acidsmentioning
confidence: 99%
“…This led the authors to conclude that metabolic changes in radiolabeled amino acid incorporation measured by PET preceded the clinical response. Studies of the distribution of [ 18 F]fluoroalanine in tissue showed that the tumor : tissue ratio increased as a function of time, suggesting that this tracer could be of interest in detecting breast cancer [98]. [ 11 C]Tyrosine seemed to visualize malignant breast tumors as effectively as 18 F-FDG, but the visual contrast was better with 18 F-FDG.…”
Section: Radiolabeled Nucleosides and Amino Acidsmentioning
confidence: 99%
“…16,17 Conversely, placing an iodine atom on the aromatic ring reportedly lowers the affinity. 23 Both 18 F-and 131 I-labeled tamoxifen analogues show high uptake by liver, 24 which interferes with the interpretation and localization of breast tumors. Other radiolabeled steroids also show higher uptake by liver and lung.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of [ 18 F]fluoroalanine (2‐amino‐3‐[ 18 F]fluoropropionic acid, 13 ) by a substitution reaction of a protected tosylserine precursor led to radiochemical yields of less than 1%, why it found no clinical application. Further examples in this series are the synthesis of 2‐amino‐4‐[ 18 F]fluoromethylsulfanylbutyric acid ([ 18 F]fluoromethionine, 14 ) and 4‐[ 18 F]fluoro‐ l ‐glutamic acid (BAY 85–8050, 15 ) …”
Section: F‐labelled Amino Acidsmentioning
confidence: 99%